Blending electronic techniques with traditional teaching methods to enhance chest X-ray interpretation in medical students - Mohsen Gholinataj Jelodar; Samaneh Mirzaei (PLoS ONE, 2025)
Introduction Medical students must possess the skill of interpreting chest X-rays, as it is vital for accurately diagnosing patients and determining the correct treatment methods. However, there is a lack of adequate reporting on satisfactory radiology interpretation skills. This study aims to examine the impact of an electronic educational program on the ability of medical students to interpret chest radiographs. Method The study is a quasi-experimental intervention involving a pre-test and post-test. It was conducted on 4th-year medical students from two academic hospitals in Yazd (from January 20, 2024, to April 20, 2024). The students were randomly assigned to either a control group or an intervention group. First, the skill level of the participants in both groups was assessed in chest radiographic interpretation using an electronic test. The training was carried out with two intervention(N = 40) and control groups(N = 38) through a 3-hour workshop held over two consecutive weeks. Following the initial training, the intervention group received an electronic educational package consisting of 59 chest radiographs. 15 chest X-rays and educational slides were sent to the students daily via Google Forms over two weeks. A month later, the student’s skills in interpreting chest X-rays were evaluated in both groups. Results In area of knowledge, the mean pre-test score for the intervention group was 2.7 (± 2.3), which increased to 14.13 (± 2.66) after the intervention. In the control group, the pre-test score rose from 3.26 (± 2.44) to 6.58 (± 3.44). These results indicate a significant increase in the knowledge score for the intervention group when compared to the control group (p < 0.001). In the need for a CT scan, the mean score for the intervention group increased significantly from 1.38 (± 1.4) in the pre-test to 9.63 (± 2.82) in the post-test. In contrast, the control group showed an increase from 1.53 (± 1.17) to 4.08(± 2.82). This indicates that the intervention had a significant effect on improving the ability to detect the need for a CT scan (p < 0.001). In the area of self-confidence, the intervention group demonstrated an increase from an average score of 26.83 (±10.23) in the pre-test to 73.9 (±18.38) in the post-test. In contrast, the control group experienced an increase from 30.37 (±11.5) to 46.18 (±18.38). These findings indicate a significant improvement in self-confidence within the intervention group following the implementation of the training program (p < 0.001). Conclusion Both traditional and blended E-learning improved students’ chest x-ray interpretation skills. However, the study found that the group receiving electronic training showed more noticeable positive changes, significantly increasing students’ self-confidence. A combination of E-learning and traditional methods significantly improves chest radiograph interpretation among young students. Early integration of E-learning for CXR interpretation in the educational curriculum is recommended.